Integration University, Service and Community: a report of an experience of the undergraduate medical course in basic assistance in the city of São Paulo - Guisardi Pereira, Juliana; Veiga Martines, Wânia Regina; Souza Leite Campinas, Lúcia de Lourdes; Sampaio Chueiri, Patricia (O Mundo da Saúde, 2009)
A new way of conceiving the teaching-learning process for health professions in undergraduate medical courses has gathered momentum in Brazil in recent years, and stimulated the implantation of several education policies, as well as initiatives of institutions of higher education and the social control in health. Such actions have been a response to the necessity of changes in the teaching-learning process due to the incapacity of the sector in solving the huge percentage of problems that affect the population. The establishment of partnerships between health professionals, teaching institutions and the community has been pointed by the literature as an important strategy to facilitate the construction of knowledge from the critical reflection on reality, the integration of practice and theory and integral assistance. The discipline Integration University, Service and Community of the medical course of São Camilo University Center has as its aim to prepare a medical professional able to act in the health-disease process in its different levels of assistance, in accordance with the epidemiological profile of the target population, promoting integral health of human beings. This study aimed to describe the implantation of practical teaching of this discipline in Basic Units of Health of the city of São Paulo, and the activities proposed to students in order to reach the theoretical-practical integration around the extended conception of the health-disease process and interdisciplinary work in basic health assistance.